Inequality in Household Adaptation to Schooling Shocks: Covid-Induced Online Learning Engagement in Real Time - Andrew Bacher-Hicks; Joshua S. Goodman; Christine Mulhern (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We use high frequency internet search data to study in real time how US households sought out online learning resources as schools closed due to the Covid-19 pandemic. By April 2020, nationwide search intensity for both school- and parent-centered online learning resources had roughly doubled relative to baseline. Areas of the country with higher income, better internet access and fewer rural schools saw substantially larger increases in search intensity. The pandemic will likely widen achievement gaps along these dimensions given schools' and parents' differing engagement with online resources to compensate for lost school-based learning time. Accounting for such differences and promoting more equitable access to online learning could improve the effectiveness of education policy responses to the pandemic. The public availability of internet search data allows our analyses to be updated when schools reopen and to be replicated in other countries.
Keywords: I20; 330; online learning; school closures; internet search; Google trends; Covid-19